Cobra; geschiedenis, voorspel en betekenis van een beweging in de kunst van na de tweede wereldoorlog. - Stokvis, W. (Amsterdam : De Bezige Bij, 1980)
Alechinsky, Pierre ; Alfelt, Else ; Appel, Karel ; Atlan, Jean-Michel ; Balle, Mogens ; Bille, Eiler ; Brands, Eugène ; Claus, Hugo ; Constant ; Corneille ; Dotremont, Christian ; Doucet, Jacques ; Ferlov, Sonja ; Gear, William ; Gilbert, Stephen ; Götz, K.O. (Karl Otto) ; Gudnason, Svavar ; Heerup, Henry ; Hultén, Carl-Otto ; Jacobsen, Egill ; Jorn, Asger ; Kemeny, Zoltan ; Van Lint, Louis ; Lucebert ; Nieuwenhuys, Jan ; Nyholm, Erik ; Ortvad, Erik ; Österlin, Anders ; Pedersen, Carl-Henning ; Rooskens, Anton ; Tajiri, Shinkichi ; Thommesen, Erik ; Wolvecamp, Theo
boek